2008
DOI: 10.1007/s12192-007-0007-z
|View full text |Cite
|
Sign up to set email alerts
|

P-Cadherin and β-catenin are useful prognostic markers in breast cancer patients; β-catenin interacts with heat shock protein Hsp27

Abstract: The cadherin-catenin proteins have in common with heat shock proteins (HSP) the capacity to bind/interact proteins of other classes. Moreover, there are common molecular pathways that connect the HSP response and the cadherin-catenin protein system. In the present study, we have explored whether in breast cancer the HSP might interact functionally with the cadherin-catenin cell adhesion system. Beta-catenin was immunoprecipitated from breast cancer biopsy samples, and the protein complexes isolated in this way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 55 publications
6
63
2
Order By: Relevance
“…Hsp27 is a molecular chaperone that can interact with other proteins. For example, in human breast cancer tissues and in a rodent breast cancer cell line, Fanelli et al (2008) reported the interaction of β-catenin with Hsp27 and with HSF1, which may explain some of the molecular pathways that affect the prognosis of breast cancer patients. A recent study reported that histone deacetylase HDAC6, transcription factor STAT2 and procaspase-3 were degraded in human cancerous cells displaying genetically decreased levels of Hsp27 suggesting that they are client proteins of Hsp27 (Gibert et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hsp27 is a molecular chaperone that can interact with other proteins. For example, in human breast cancer tissues and in a rodent breast cancer cell line, Fanelli et al (2008) reported the interaction of β-catenin with Hsp27 and with HSF1, which may explain some of the molecular pathways that affect the prognosis of breast cancer patients. A recent study reported that histone deacetylase HDAC6, transcription factor STAT2 and procaspase-3 were degraded in human cancerous cells displaying genetically decreased levels of Hsp27 suggesting that they are client proteins of Hsp27 (Gibert et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, we still noted that some of the included studies (Lin et al, 2000;Fanelli et al, 2008;Xu et al, 2012;Li et al, 2014) defined either cytoplasm or nucleus as positive β-catenin expression, which made it difficult to explain which part of accumulation of β-catenin played the most important influence on prognosis in BC patients, only to find that positive β-catenin expression by this definition has significant association with OS. This result confirms our conclusion that β-catenin expression in cytoplasm/ nucleus, which is considered to be indicative of Wnt pathway activation, was significantly associated with an unfavorable prognosis in patients with BC.…”
Section: Sensitivity Analysismentioning
confidence: 95%
“…Alteration of molecular biological markers in tumor tissues has become an important part in predicting the prognosis of patients with BC and seemed more specific than markers currently used in clinical such as TNM stage, weight loss and lymph node metastasis. There are many reports about the prognostic significance of β-catenin in BC (Lin et al, 2000;Gillett et al, 2001;Lim and Lee, 2002;Chung et al, 2004;Dolled-Filhart et al, 2006;Nakopoulou et al, 2006;Park et al, 2007;Fanelli et al, 2008;Paredes et al, 2008;Khramtsov et al, 2010;Kim et al, 2010;Logullo et al, 2010;Lopez-Knowles et al, 2010;Geyer et al, 2011;Cheng et al, 2012;Mukherjee et al, 2012;Xu et al, 2012;Ho et al, 2013;Pang et al, 2013;Weissenbacher et al, 2013;Li et al, 2014). However, results were inconsistent.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 2 more Smart Citations